Doctor Who. The complete first series [videorecording (Blu-Ray)] - Gold, Murray, 1969- (BBC Worldwide, 2013)
In the new Doctor Who series, London shop assistant Rose Tyler embarks on adventures through time and space with a mysterious alien known as "The Doctor," encountering strange lifeforms and protecting the Earth from alien invaders.